2012
DOI: 10.3892/ol.2012.990
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid variant of urothelial carcinoma: Cytological analysis of three cases

Abstract: Abstract. Sarcomatoid variant of urothelial carcinoma (SV-UC) is characterized by the presence of biphasic malignant neoplastic components exhibiting morphological and/or immunohistochemical evidence of epithelial and mesenchymal differentiation. SV-UC is a rare variant of UC and the cytological features of this tumor have not been well described. In the present study, we analyzed the cytological features of a series of SV-UC cases; 6 voided urine specimens from 3 patients with SV-UC were reviewed. Several cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Arita et al [47] reported their study which included the first analysis of cytological features from a series of sarcomatoid variant of urothelial carcinoma and discussed possible differential diagnostic considerations. They analysed and reviewed the cytological features of a series of sarcomatoid variant of urothelial carcinoma cases which included 6 voided urine specimens from 3 patients with sarcomatoid variant of urothelial carcinoma.…”
Section: Discussion and Narrations From Some Of The Reported Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Arita et al [47] reported their study which included the first analysis of cytological features from a series of sarcomatoid variant of urothelial carcinoma and discussed possible differential diagnostic considerations. They analysed and reviewed the cytological features of a series of sarcomatoid variant of urothelial carcinoma cases which included 6 voided urine specimens from 3 patients with sarcomatoid variant of urothelial carcinoma.…”
Section: Discussion and Narrations From Some Of The Reported Casesmentioning
confidence: 99%
“…Arita et al [ 47 ] stated that the cytological features of sarcomatoid variant of urothelial carcinomas are not well known and only one cytological analysis of sarcomatoid variant of urothelial carcinoma had previously been reported. Arita et al [ 47 ] reported their study which included the first analysis of cytological features from a series of sarcomatoid variant of urothelial carcinoma and discussed possible differential diagnostic considerations. They analysed and reviewed the cytological features of a series of sarcomatoid variant of urothelial carcinoma cases which included 6 voided urine specimens from 3 patients with sarcomatoid variant of urothelial carcinoma.…”
Section: Discussion and Narrations From Some Of The Reported Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-recognized that cytological examination of urine specimens has high sensitivity for detection of conventional high-grade urothelial carcinoma ( 10 ). Additionally, the cytological features of rare histopathological variants of urothelial carcinoma, such as micropapillary, nested and sarcomatoid, have also been described ( 11 16 ). However, prostate cancer cells are rarely identified in the urinary cytological specimen ( 17 ), and it has been recognized that routine examination of urine cytology for detection of prostate cancer is not recommended due to low sensitivity ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatoid carcinoma has been reported in a variety of organs, including the urinary bladder (11,12), kidney (13) and female genital tract (14). RPSC is an extremely rare entity, with only 14 confirmed cases reported in the literature since 1961 (19).…”
Section: Discussionmentioning
confidence: 99%